The daily production of Soviet women during the Great Patriotic War (on the example of Ishim Shoe Factory No. 4) - A. A. Frolova (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the reconstruction of the daily life of female workers of the Ishim shoe factory No. 4 during the Great Patriotic War. To study the everyday life of women during the war years, the office documents of the factory and local authorities, as well as documents of personal origin, are used. The study is based on a historical and anthropological approach to the past. Descriptive method and oral history method are applied. The author comes to the conclusion that thanks to the efforts of women, who were the main labor force of the factory, in a short time the evacuated enterprise not only began to function in a new place, but also became a model for other enterprises of the Ishim region. The women not only over fulfilled the plan for sewing shoes, but also fully met the production needs of the enterprise: they prepared peat and firewood organized vegetable gardens and stored vegetables for the factory canteen. In addition, women were actively involved in social work taking care of the evacuees, collecting money, food and warm clothes for the needs of the front. Along with the development of new social roles by women, they retained their traditional responsibilities related to maintaining a home and raising children. Similar transformations in the social behavior of women occurred against the background of a deterioration in living conditions, a reduction in living standards, a lack of nutrition, and complications of the epidemiological situation. With the complication of her social roles, a woman during the war years carried an important social function associated with the creation of a special spiritual atmosphere, simultaneously reconciling with the brutal military reality and maintaining the hope of a return to peacetime